Aerosol pH Dynamics During Haze Periods in an Urban Environment in China: Use of Detailed, Hourly, Speciated Observations to Study the Role of Ammonia Availability and Secondary Aerosol Formation and Urban Environment. Issue 16 (20th August 2019) - Shi, Guoliang; Xu, Jiao; Shi, Xurong; Liu, Baoshuang; Bi, Xiaohui; Xiao, Zhimei; Chen, Kui; Wen, Jie; Dong, Shihao; Tian, Yingze; Feng, Yinchang; Yu, Haofei; et al.
Abstract: Aerosol pH is a useful diagnostic of aerosol chemistry for formation of secondary aerosol and has been hypothesized to be a key factor in specific chemical reaction routes producing sulfate and nitrate. In this study, we measured hourly concentrations of water‐soluble ions in particulate matter with an aerodynamic diameter less than 2.5 μm, along with gaseous pollutants in Tianjin, China, from 4 to 31 January 2015. The following source contributions to water‐soluble ions were estimated by positive matrix factorization: secondary sulfate (13%), secondary nitrate (44%), coal (14%), vehicle (16%), and dust (13%). ISORROPIA‐II was used to investigate the complex relationships among aerosol pH, ammonia, and secondary aerosol formation. The estimated hourly aerosol pH varied from −0.3 to 7.7, with an average of 4.9 (±0.78); the median value was 4.89, and the interquartile range was 0.72. During less polluted conditions, aerosol pH ranged from less than 0 to about 7; during heavily polluted conditions, pH was close to 5 (3.9–7.9) despite large amounts of sulfate. Sufficient ammonia/ammonium was present to balance high sulfate and nitrate formation. NH4 + /NH3 (g) helped stabilize pH while nonvolatile cations contributed less to decreasing aerosol acidity. High acidy (pH < 3), light pollution (total water soluble ions < 30 μg/m 3 ), and low water content (less than 5 μg/m 3 ) were more correlated with higher rates of sulfate formation than nitrate formation in the winter. Plain Language Summary: Megacities in China and elsewhere experience very smoggy days that get continuously worse during haze episodes. The high levels of smog are created both from directly emitted particles and the formation of more particulate matter from gas‐phase reactions. Scientists are not able to fully explain how so much smog is formed so rapidly during intense haze periods. Ammonia was found to stabilize the acidity of the aerosols, but the aerosols remained acidic with pH of around 4. Here detailed hourly measurements of many species are used to elucidate the importance of ammonia, which can potentially neutralize acidic gases and aqueous particles. Key Points: NH4 + /NH3 and pH had a more nonlinear relationship during highly polluted periods, compared to less polluted periods NH4 + /NH3 (g) was important for stabilizing pH during the heavily polluted periods SOR was higher than NOR under conditions with high acidity, light pollution, and low water content in the winter